ANALYSIS OF THE ROLE OF MFI AND FAMILY FUNDING ON WELFARE MADURA SALT FARMERS - Arie Setyo Dwi Purnomo; Moh Zaki Kurniawan (Jurnal Ilmiah Global Education, 2023)
Basically, financial service institutions in the form of microfinance institutions (MFIs) are needed to support rural economic development, especially as institutions to facilitate the costs of salt farming businesses. This is because most farmers face technology adoption due to weak capital. This condition occurs in salt farmers, Kalianget District, Sumenep Regency. This study aims to determine the concept of salt business. factors that affect the productivity of salt business, and the role of microfinance in salt farming. The study was conducted in the village of Kertasada with the aim of using a purposive sampling method with a total of 45 samples. The data obtained from the study were analyzed using R/C and Cobb-Douglass functions. The results showed that salt farmers were profitable with an R/C value >1, salt production was significantly affected by labor, weather and family funding